Compostos bioativos e atividades antioxidante na pós-colheita do buriti em diferentes estádios de maturação - Lima, Jéssica Milanez Tosin (2016)
The fruit of the buriti pulp has yellow-orange color , it has bittersweet flavor with starchy and oily consistency , involving cancellous cored . It has hard shell , formed by small scales reddish -brown color. Aimed to the project execution perform chemical , physico-chemical and functional characterization of M. flexuosa L. fruits in order to support the technological development of culture in Roraima. The fruits were harvested in the savanna / forest transition environment, in particular farms. After harvest , the fruits were selected and standardized , considering the external appearance ( skin color and plant health ) , subsequently sanitized. Those selected were submitted fresh mass analysis, pH, soluble solids, pectin content, enzyme activity pectinametilesterase (PME) and polygalacturonase (PG), respiratory behavior (CO2 and ethylene ) and functional activity with evaluation of phenolic compounds, carotenoids and antioxidant activity (ORAC and DPPH). Finally, we observed high antioxidant activity in the fruit during three harvest and during the storage period characterized by high levels of phenolics and carotenoids. The fruits of the harvest 1 and 2 were those who had higher post-harvest life. The climacteric profile was observed during the storage period, found by peak respiration and ethylene production. In this sense, changes occurred as pH, SS, AT, as well as in the activity of peptic enzymes and reduction in total pectin content. The levels of phenolic compounds, carotenoids and antioxidant activity were satisfactory, thus confirming the functional potential of these fruits.